Chemical reaction engineering of nutritional phenomena in the human body - Chen, Xiao Dong (Frontiers in Chemical Engineering, 2024)
Unlike many accomplished fields, human nutrition seems lacking the support of engineering science. Here, the aspects of food processing in the gastro-intestinal (GI) tract are reviewed briefly highlighting the experimental CRE approach to digestion studies in particular. As a first to look at human nutrition in terms of conservation laws, the differential forms of mass and energy balances are presented, emphasizing the chemical and biochemical reaction rates of generation and consumption, and the heats associated with these reactions respectively. These rates and the heats should be very meaningful for understanding the dynamics of nutrition within the body, though they remain unknown. Without solving the differential equations, global integrations of the mass balances within each organ up to the organ boundary, can create control volumes for gaining new insights. The transient multicomponent nature of the stomach 'reactor' emptying for instance. Global integration within the human body to the boundaries of the entire GI tract, from mouth to anus, leaves the GI tract to be a 'pipe outside the body'. This has revealed interesting aspects, highlighting the human body as a 'molecular machine'. It is envisaged that the terms outlined here ought to be established in future for improving human nutrition.